Water Quality and Sediment Characteristics of the Rajang River at the Pelagus Area and Its Tributary - Angela Sanoh, Tawan (Universiti Malaysia Sarawak(UNIMAS), 2018)
Water quality and sediment characteristics in the downstream river of a hydroelectric dam may be affected by the dam operation or other activities surrounding the river. Little is known about the water quality and sediment characteristics of the Rajang River at the Pelagus area. As a hydroelectric dam was planned to be built in the area in the future, it is important to collect baseline data for future reference. Therefore, this study was conducted to mainly document the water quality and sediment characteristics along the Rajang River and its tributaries at the Pelagus area and The water quality changes due to changes in water discharge from the Bakun dam upstream and rainfall amount. A total of 30 stations were selected for the study which consisted of a total of 9 stations at upstream (St 1-9), 10 stations at midstream (St 10-19) and 11 stations at downstream (St 20-30) sections. The total length of the main Rajang River covered was approximately 130 km. For comparisons based on different water discharges, 11 stations at downstream area of the Pelagus Area were sampled three times. The results of the present study show that DO have an increasing trend from upstream toward downstream direction. The BOD was higher than 3 mg/L at most of the stations at Rajang River at upstream (4.29 – 4.91 mg/L) and downstream sections during January 2016 (4.58 – 5.03 mg/L) but not at the midstream section in December 2015 (2.31 – 2.61 mg/L), midstream sections in July 2015 (2.61 – 3.67 mg/L) and in March 2016 (2.27 – 2.56 mg/L). These were greatly influenced by the weather condition and the volume of discharge from Bakun Hydroelectric Dam. The means of conductivity, turbidity, transparency, TSS, pH, DO, and NH3-N of the tributaries have significantly higher concentrations compared to the main river stations along the Rajang River, thus, influencing the water quality of the Rajang River. The amount of water discharge from the spillway of the Bakun Hydroelectric Dam influenced the DO, BOD and COD values at the stations in Rajang River. The DO values at Rajang River deteriorated due to no water discharge from the spillway at the time of sampling in January 2016. Thus, increased concentrations of BOD and COD were observed among the stations at Rajang River. In terms of water quality index (WQI), the stations were classified as Class II or III and their status were considered clean or slightly polluted. Meanwhile, the textural class of sediments in Rajang River area ranged from sand, clay, sandy clay loam, sandy loam to silt. Comparatively, the mean pH of sediment shows that the sediment is more acidic (6.18) than water (6.90). The sediment characteristics results in Rajang River and its tributaries are: pH (4.50 to 6.70), TOC (0.01 to 0.9%), OM (0.32 to 5.20%), TKN (56.51 to 1597.30 mg/kg) and TP (41.41 to 120.40 mg/kg). There are significant correlations between water and sediment parameters. They are river water pH and sediment TP, sediment TP and water DO and temperature with sediment TKN. The land use such as logging and plantation activities, domestic and household waste water also influenced the water quality parameters. This study shows that the water parameters of Rajang River were influenced by the loading of pollutants from the tributaries particularly water turbidity and TSS; and sediment silt, TP and TKN. The spillway and turbine discharge from Bakun Dam changes the water quality significantly.